Enhanced water production and improving solar water distillation efficiency of double-slope solar stills: Modeling and validation - Almajali T.A.H.; Ismail F.B.; Kazem H.A.; Gunnasegaran P.A.L.; AL Shurafa S.M.; Al-Muhsen N.F.O. (Elsevier Ltd, 2025)
Solar distillation is a promising technology for producing clean water using renewable energy, especially in regions with water scarcity and contamination. This study investigates the impact of design modifications on the efficiency of a double-slope solar still coupled with evacuated tubes and external reflectors. Using Matlab software analysis, key findings indicate that packing factors, temperature control, and solar radiation exposure all contribute to the system's optimal performance. Solar radiation levels directly correlate with production rates, emphasizing the need for effective sunlight exposure. The system's ability to rely on stored heat at night enhances its practicality. This study shows how to make solar stills more efficient at producing clean water. It is found that the best way to do this is to use PV cells with a packing factor of 0.25. A packing factor of 0.25 outperforms other factors, significantly increasing water production and system efficiency. With this optimal factor, the system achieved a remarkable thermal efficiency of 83.5 % and a maximum daily production of 19 L per square meter during peak solar radiation hours. The system's overall efficiency is 94 % increased by 13 % over the highest value recorded in previous studies. Furthermore, the system's productivity increased by 40 % from the highest value recorded in previous studies. The amount of electrical energy produced is directly proportional to the packing factor, by the power of 41.1 W-hours (Wh) at a PV cell with a packing factor of 0.25. ? 2024 Elsevier Ltd